Calling on the name of the Lord : a biblical theology of prayer - Millar, J. G. (Downers Grove : InterVarsity Press, 2016)
"At that time people began to call upon the name of the LORD" (Genesis 4:26 ESV). From this first mention of prayer in the Bible, right through to the end, when the church prays "Come, Lord Jesus!" (Revelation 22:20), prayer is intimately linked with the gospel?God's promised and provided solution to the problem of human rebellion against him and its consequences. After defining prayer simply as "calling on the name of the Lord," Gary Millar follows the contours of the Bible's teaching on prayer. His conviction is that even careful readers can often overlook significant material because it is deeply embedded in narrative or poetic passages where the main emphases lie elsewhere. Millar's initial focus is on how "calling on the name of the Lord" to deliver on his covenantal promises is the foundation for all that the Old Testament says about prayer. Moving to the New Testament, he shows how this is redefined by Jesus himself, and how, after his death and resurrection, the apostles understood "praying in the name of Jesus" to be the equivalent new covenant expression. Throughout the Bible, prayer is to be primarily understood as asking God to deliver on what he has already promised?as Calvin expressed it, "through the gospel our hearts are trained to call on God's name" (Institutes 3.20.1). This New Studies in Biblical Theology volume concludes his valuable study with an afterword offering pointers to application to the life of the church today. Addressing key issues in biblical theology, the works comprising New Studies in Biblical Theology are creative attempts to help Christians better understand their Bibles. The NSBT series is edited by D. A. Carson, aiming to simultaneously instruct and to edify, to interact with current scholarship and to point the way ahead. -- Amazon
The day prayer began: prayer in the Pentateuch -- Big prayers and the movements of history : prayer in the former prophets -- Praying in the light of the future: prayer in the latter prophets -- Praying for a new covenant: prayer in the writings -- The psalms, the Messiah, and the church -- Jesus and prayer: prayer in the Gospels -- The church at prayer: prayer in the book of Acts -- Church planting and prayer: prayer in Paul's letters -- The end of prayer: prayer in the later New Testament -- Afterword: why this matters - (re)learning to pray big prayers
Includes bibliographical references and index.
Keywords: Prayer -- Biblical teaching; Prayer -- Christianity